EXAMINING SWEAR WORDS IN FURY (2014): A SOCIOLINGUISTIC ANALYSIS OF CHARACTER LANGUAGE - Muziatun, Muziatun; Malabar, Fahria; Susan, Eri (Media Inovasi Pendidikan dan Publikasi, 2024)
This research analyzes the use of swear words in the 2014 film Fury, directed by David Ayer. It explores the types of swear words used by characters and the sociolinguistic factors triggering their usage. Language serves as a dynamic medium for expressing emotions, norms, and culture; Thus, understanding its variations is crucial, especially among youth who frequently use toxic language. The study adopts Andersson's (1992) classification of swear words into four types: expletive, abusive, humorous, and auxiliary. Additionally, it employs Staley's (1978) framework to identify social triggers for swearing, such as emotional expression and social bonding. The film's portrayal of American soldiers during World War II illustrates how extreme circumstances can normalize the use of profane language. This research aims to enhance awareness of sociolinguistic dynamics in contemporary discourse, emphasizing the importance of context in the interpretation of swearing. The findings will provide insights for English language educators and students, highlighting the need for understanding cultural nuances in language use. Ultimately, this study seeks to foster responsible communication practices while recognizing the role of swear words in everyday interactions and social contexts.